Au-delà du mur du son, l’univers consonant et dissonant d’Anne Lauber - Cloutier, Diane (La Scène musicale, 1984)

La musique de salon au Québec (1880-1915) - Geoffrion, Diane (Les Cahiers de l'ARMuQ, 1984)

Emma Albani: Victorian Diva - MacDonald, Cheryl (Dundurn Press, 1984)
Talented Emma Albani was a favourite of Queen Victoria, singing at Victoria's funeral as well as Edward VII's coronation, and for many other heads of state from Russia, Austria, France, Italy, Belgium, Denmark, United States and Canada. Sir Arthur Sullivan, Gounod, Von Flotow and Dvorak wrotemusic for her and she sang with Nellie Melba, Adelina Patti, Jean de Reszke, Francesco Tamagno among others. Emma, who married Ernest Gye, manager of Covent Garden, was celebrated as one of the leading operatic and oratorio sopranos of the century. Emma (Lajeunesse) Albani, one of Canada's first internationally known performers, began as a student singing in a Chambly, Quebec convent and an Albany, New York church. From her opera debut in April 1870 in Sicily to her farewell concert in October 1911 in London, England, she was loved for her voice as well as her kindness, which was rare in a prima donna. She was adored by fans world-wide as George Bernard Shaw recorded in 1889," ... people were standing two and three deep behind the chairs ..., consisting of prima donna worshippers who are bent on obtaining a bird's eye view of Madam Albani.